2014
DOI: 10.11118/actaun201159010153
|View full text |Cite
|
Sign up to set email alerts
|

Changes in isoflavones concentrations in cheese during processing and ripening

Abstract: The aim of the study was to determine possible changes in isoflavones concentration in cheese made from either control or isoflavone-enriched milk during manufacturing and ripening. The experiment was carried out on four high-yielding lactating Holstein cows that were divided into two groups with similar mean milk yield. The control group of cows was fed a diet based on extruded rapeseed cake (C) while the experimental group of animals was fed a diet based on extruded full-fat soya (S). The experiment was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
1
14
2
Order By: Relevance
“…As indicated in the introduction section, the content of phytoestrogens in kefir samples has not been reported up to now since these compounds have not been previously analyzed in such matrices. Regarding cheese samples, the obtained results, in the range of 1.76-46.7 g/kg for daidzein, glycitein and enterolactone, are comparable to the content previously determined by Křížová et al [7] who reported values around 11.7-30.5 g/kg for daidzein, genistein and glycitein, and slightly lower that the data reported by Kuhnle et al [6] who found enterolactone in concentrations of 30-230 g/kg in different type of cheese products. As it was demonstrated by Křížová et al [7], these differences can be associated with the animal diet as well as the type of process applied to each product which can modify considerably the initial level of phytoestrogens present in the raw material used for its preparation.…”
Section: Analysis Of Real Samplessupporting
confidence: 89%
See 4 more Smart Citations
“…As indicated in the introduction section, the content of phytoestrogens in kefir samples has not been reported up to now since these compounds have not been previously analyzed in such matrices. Regarding cheese samples, the obtained results, in the range of 1.76-46.7 g/kg for daidzein, glycitein and enterolactone, are comparable to the content previously determined by Křížová et al [7] who reported values around 11.7-30.5 g/kg for daidzein, genistein and glycitein, and slightly lower that the data reported by Kuhnle et al [6] who found enterolactone in concentrations of 30-230 g/kg in different type of cheese products. As it was demonstrated by Křížová et al [7], these differences can be associated with the animal diet as well as the type of process applied to each product which can modify considerably the initial level of phytoestrogens present in the raw material used for its preparation.…”
Section: Analysis Of Real Samplessupporting
confidence: 89%
“…As it was indicated in the introduction section, only a few studies have been published regarding the evaluation of estrogenic compounds in milk or milk derivatives [6,7,[17][18][19][26][27][28][29] except for kefir samples, which has not been previously analyzed. Concerning cheese samples, it should be indicated that it has only been previously analyzed to determine phyto-, natural and synthetic estrogens, but not mycoestrogens [6,7,17,18]. In this sense, Guoliang et al applied a simple solvent extraction procedure followed by HPLC-FD with a previous derivatization with ethyl-acridinesulfonyl chloride for the determination of E 1, E 2 and E 3 among other type of compounds.…”
Section: Comparison With Other Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations